2013
DOI: 10.1007/s00421-013-2639-2
|View full text |Cite
|
Sign up to set email alerts
|

Aging impairs PI3K/Akt signaling and NO-mediated dilation in soleus muscle feed arteries

Abstract: We tested the hypothesis that impaired nitric oxide (NO)-mediated, endothelium-dependent dilation in aged soleus muscle feed arteries (SFA) is due to an age-related decline in the potential for PI3-kinase (PI3K)/protein kinase B (Akt)-dependent phosphorylation of endothelial NO synthase (eNOS) on serine residue 1177 (p-eNOS(ser1177)). SFA from young (4 months) and old (24 months) Fischer 344 rats were cannulated for examination of endothelium-dependent [flow or acetylcholine (ACh)] and endothelium-independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…However, it has been suggested that ROS signaling is necessary for endothelium-dependent vasodilation in muscle feed arteries from young and aged rats (Sindler et al, 2013) and H2O2-induced vasodilation of aged muscle arterioles is blunted (Trott et al, 2011). On the other hand, it has been also proposed that impaired NO signaling in aged muscle feed arteries could be related to ineffective NO production due to reduced NOS activation (Trott et al, 2013) or insufficient co-factor (tetrahydrobiopterin) availability (Delp et al, 2008).…”
Section: Aging-induced Alterations Of Skeletal Muscle Perfusionmentioning
confidence: 92%
“…However, it has been suggested that ROS signaling is necessary for endothelium-dependent vasodilation in muscle feed arteries from young and aged rats (Sindler et al, 2013) and H2O2-induced vasodilation of aged muscle arterioles is blunted (Trott et al, 2011). On the other hand, it has been also proposed that impaired NO signaling in aged muscle feed arteries could be related to ineffective NO production due to reduced NOS activation (Trott et al, 2013) or insufficient co-factor (tetrahydrobiopterin) availability (Delp et al, 2008).…”
Section: Aging-induced Alterations Of Skeletal Muscle Perfusionmentioning
confidence: 92%
“…Similarly, in soleus muscle 1A arterioles, age-induced imbalance in signalling mediated by reactive oxygen species, including superoxide radicals, hydrogen peroxide and peroxynitrite contributes to impairment of endothelium-dependent dilatation to acetylcholine (Sindler et al 2013). Impairment of PI3-kinase activity also appears to contribute to age-induced loss of endothelium-dependent, NO-mediated vasodilatation in soleus muscle feed arteries (Trott et al 2013). In contrast, loss of prostacyclin-mediated vasodilatation is an important contributor to age-induced impairment of flow-induced vasodilatation in gastrocnemius muscle arterioles (Spier et al 2007).…”
Section: Vasodilatory Responsivenessmentioning
confidence: 98%
“…In locomotory skeletal muscle, vasodilatory responses differ between arterioles of highly oxidative muscle and arterioles of highly glycolytic muscle (McCurdy et al 2000;Wunsch et al 2000;Aaker & Laughlin, 2002). The preponderance of data indicate that age-induced alterations of vasodilatory responses occur due to changes within the endothelium, whereas vasodilatory responses of the vascular smooth muscle that are endothelium independent are generally preserved with age (Muller- Delp et al 2002c;Woodman et al 2002;Spier et al 2004Spier et al , 2007Sindler et al 2009;McCullough et al 2011;Trott et al 2011Trott et al , 2013. Because the endothelium is the interface between the flowing blood and the vascular smooth muscle, it is especially important to consider the haemodynamics present at varying points along the vascular tree within muscle and the haemodynamic signals created within muscles with different functional responses during activity or exercise.…”
Section: Vasodilatory Responsivenessmentioning
confidence: 99%
See 2 more Smart Citations